Hubungan Motivasi Dan Disiplin Kerja Terhadap Produktivitas Pegawai Pada Kantor Kecamatan Awayan Kabupaten Balangan (Fakultas Ekonomi Universitas Gresik, 2023)
In era this time, time is valuable commodities, therefore behaviour discipline that cover discipline work. Very need for every individual. But practically not all has work ethic both for government resort, this matter one of them happen because discipline their work varies. Also realize that civil service problem be vast problem and many the aspects. Motivation that can spur on also be one of the factor can not less important in influence progress and success a organization. Itself work spirit explanation big the so small effort that given from certain sides to motivating in carry out the duties. Elements found in motivation belongs higher, work friend, physical tool, policy and organization regulation and other as it. Marginally human in company necessary defend the alive continuance, to bloom and get profit. To achieve that thing, so wanted motivation and work spirit in run performance process. Discipline soul must has in every civil public servant especially in carry out various job at district office work environment Awayan regency Balangan. Remember that discipline work closely related with work motivation, so researcher interested to canvass farther about connection between work motivation with discipline work that influence tall or the low district office official work productivity level Awayan regency Balangan.